Severe acute respiratory syndrome coronavirus 2 detection by real time polymerase chain reaction using pooling strategy of nasal samples - Pratelli, Annamaria; Pellegrini, Francesco; Ceci, Luigi; Tatò, Daniela; Lucente, Maria Stella; Capozzi, Loredana; Camero, Michele; Buonavoglia, Alessio (Frontiers in Microbiology, 2022)
COVID-19 is a life-threatening multisistemic infection caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Infection control relies on timely identification and isolation of infected people who can alberg the virus for up to 14 days, providing important opportunities for undetected transmission. This note describes the application of rRT-PCR test for simpler, faster and less invasive monitoring of SARS-CoV-2 infection using pooling strategy of samples. Seventeen positive patients were provided with sterile dry swabs and asked to self-collected 2 nasal specimens (#NS1 and #NS2). The #NS1 was individually placed in a single tube and the #NS2 was placed in another tube together with 19 NSs collected from 19 negative patients. Both tubes were then tested with conventional molecular rRT-PCR and the strength of pooling nasal testing was compared with the molecular test performed on the single NS of each positive patient. The pooling strategy detected SARS-CoV-2 RNA to a similar extent to the single test, even when Ct value is on average high (Ct 37–38), confirming that test sensibility is not substantially affected even if the pool contains only one low viral load positive sample. Furthermore, the pooling strategy have benefits for SARS-CoV-2 routinary monitoring of groups in regions with a low SARS-CoV-2 prevalence.